Virtual Reality Technology and Speech Analysis for People Who Stutter - Al-Nafjan, Abeer; Alghamdi , Najwa; Almudhi , Abdulaziz (EMITTER International Journal of Engineering Technology, 2021)
Virtual reality (VR) technology provides an interactive computer-generated experience that artificially simulates real-life situations by creating a virtual environment that looks real and stimulates the user’s feelings. During the past few years, the use of VR technology in clinical interventions for assessment, rehabilitation and treatment have received increased attention. Accordingly, many clinical studies and applications have been proposed in the field of mental health, including anxiety disorders. Stuttering is a speech disorder in which affected individuals have a problem with the flow of speech. This can manifest in the repetition and prolongation of words or phrases, as well as in involuntary silent pauses or blocks during which the individual is unable to produce sounds. Stuttering is often accompanied by a social anxiety disorder as a secondary symptom, which requires separate treatment. In this study, we evaluated the effectiveness of using a VR environment as a medium for presenting speech training tasks. In addition, we evaluated the accuracy of a speech analyzer module in detecting stuttering events.